Understanding levels of sexual prejudice using mixed methods - Foy, Joelyn K. (My University, 2014)
Between February 2008 and June 2013, at least according to U.S. national media, twenty-seven young men and two young women, ranging in ages from 11 to 19, committed suicide based on their perceived or actual gender or sexual variance. Sexual minority youth are bullied more frequently than heterosexual youth, resulting in lower grade point averages and higher absenteeism. Youth who are victimized are less likely to attend college (GLSEN, 2010; Robinson & Espelage, 2011). Communities and society as a whole suffer from the economic and mental health consequences of bullying in school environments (Foy, 2012). Since teachers spend approximately twice as much time face-to-face time with children than parents (Allard & Janes, 2008), the influence of teachers on sexual minority youth cannot be overstated. Therefore, the purpose of my research was threefold: •To explore K-12 pre-service and in-service teachers’ beliefs and attitudes toward sexual minorities; •To discover whether K-12 pre-service and in-service teachers had experiences with sexual minorities; •To shed light on the role of teacher educators in preparing teachers for gender and sexually variant students in their classrooms.
Keywords: Sexual minorities; In-service teachers; Sexual prejudice